Euro Area Policies : Selected Issues Paper. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Selected Issues paper on Euro Area Policies 2013 Article IV Consultation highlights the monetary transmission mechanism and monetary policies. The European Central Bank has announced the Outright Monetary Transactions framework to address severe distortions in sovereign bond markets and safeguard monetary transmission. The cost of unsecured bond issuance remains elevated for both core and periphery banks, but there is a growing divergence between the two, driven mainly by rising periphery spreads. Weak growth and high levels of private balance sheet debt in the periphery are weighing on the health of bank balance sheets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet